Effective bond length of CFRP sheets externally bonded to concrete beams under marine environment. (10th April 2018) - Fazli, Hamed; Mohd Yassin, A.Y.; Shafiq, Nasir; Teo, Wee
Highlights: A new model for effective bond length under the marine condition is developed. Both CFRP stiffness and concrete strength had influence on effective bond length. Exposure condition had low effect on the epoxy performance between CFRP-concrete. Abstract: Externally strengthened marine concrete structures by using carbon fiber-reinforced polymer (CFRP) are being used more extensively because of their exceptional properties, including high corrosion/environmental degradation resistance. Debonding of CFRP sheet from the concrete substrate is one of the typical failure modes observed by using this technique. Therefore, the strengthening technique efficiency strongly depends on the effectiveness of the CFRP-concrete bond. Numerous experimental studies have been conducted to investigate the bond behavior and most of the proposed bond strength models considering the influence of the effective bond length. This study was conducted to experimentally investigate the effective bond length of CFRP sheets subjected to marine environment exposure, which is identified as one the major gaps in this discipline. The concrete beam specimens exposed to marine environment were tested to determine the effective bond length. The three-point bending-type shear bond test was used to obtain the stress versus load relationship. The test variables were the type and exposure duration. The test results showed that the marine environmental exposure significantly influenced bond stress and effective bond length. Two factors, CFRP stiffness and concrete compressive strength, contributed to fix the effective bond length of the CFRP-concrete interface. The maximum bond stress, after 12 months of wet/dry cyclic exposure, was found higher than that subjected to full immersion exposure. The average maximum bond stress decreased with an increase in full-immersion exposure time to 12 months. Results indicated that the exposure condition influences the capacity of CFRP-concrete bond and resulted in a reduction in effective bond length by 16–29%. Moreover, debonding was observed as the dominating mode of failure for all tested specimens. The prediction models of effective bond length, considering the influence of marine environment, are also established. Therefore, the outcome of this study will help to resolve one of the debonding issues in strengthening marine structures.